Abolishing the wealth tax: A case study for Germany - Alena Bachleitner (Austrian Institute of Economic Research (WIFO), 2017)
Since the 1990ies several countries abolished the wealth tax, but surprisingly few scholars investigated the effects empirically. Motivated by the theoretical literature, this study estimates the effect of the abolition of the net wealth tax in Germany in 1997 on the household saving rate. The use of the Synthetic Control Method allows using variables on aggregate level instead of microeconometric panel data, to estimate the effect of abolishing the net wealth tax. As a result, the analysis shows that the abolition of the net wealth tax had a clear positive effect on the German household saving rate. After three years, the saving rate was found to be about 3 percentage points higher than it would have been without the measure. Robustness checks support the results. These findings suggest that empirically the substitution effect dominated.
Keywords: 330; Wealth Tax; Abolition of Wealth Tax; Germany; Synthetic Control Method